Parenting Support for Diverse Populations - Sheshko, Dana (Université d'Ottawa / University of Ottawa, 2021)
The overarching goal of this dissertation is to inform evidence-based supports for diverse parents. Past meta-analyses (e.g., Dimitrova, Chasiotis, & van de Vijver, 2016; Porter & Haslam, 2005) have examined adjustment in migrant children, adolescents, and adults. To date, reviews have often examined only immigrants or refugees, with few quantitative comparisons between groups. Further, few include information on parenting or parental adjustment (e.g., van Os, Kalverboer, Zijlstra, Post, & Knorth, 2016). To fill this gap, I conducted a systematic review and meta-analysis of studies that used psychometrically strong measures of adjustment and parenting with newcomer immigrant and refugee families to update the literature and to provide a quantitative comparison between migrant groups. Database searches yielded 18,139 abstracts for screening; 4,626 full text articles were reviewed; 31 independent samples 25 of which have not been included in previous reviews met inclusion criteria. Results highlight important differences between migrant groups and informants: parent reports of youth adjustment generally reported greater problems among both immigrant and refugee youth compared to normative samples, whereas youth self-reports varied by migrant group (with refugee youth reporting greater problems than immigrant youth) and adjustment construct. In my second study, I developed and evaluated a self-report measure of adherence to an evidence-based parenting program that is used with diverse families. This tool, the Practitioner Session Reflection Tool (PSRT; Sheshko, Lee, & Gagné, 2015), was designed to support practitioners’ adherence to both the session content and to the primary process of self-regulation theorized to underpin the Triple P – Positive Parenting Program (Sanders, 1999, 2012). Fifty-two practitioners from 12 community agencies submitted 361 self-reports; a subset of 23 practitioners submitted 63 audio-recordings to permit additional ratings by a coding team providing a multi-informant and multimethod evaluation of adherence. Results provided preliminary evidence of good levels of reliability and validity for scores on the adherence measures. Consistent with previous research there were low correlations between informants: practitioners reported both higher content (84.6% compared to 49.9%) and process (80.0 – 95.0% compared to 30 – 55%) adherence than that rated by coders. Possible explanations for this discrepancy are discussed. Taken together, the results of these two studies highlight both the importance of offering supports that can be delivered flexibly to suit the needs of diverse families, and the need to support practitioners’ self-reflection on adherence to program content and underlying processes in delivering those supports.
Keywords: Immigrant; Refugee; Adjustment; Parenting; Meta-analysis; Adherence; Measure development; Multiple informants